Driving growth - Jeraj, Mitja (Advances in business related scientific research journal, 2025)
Small and medium-sized enterprises (SMEs) are central to economic development, yet their growth is increasingly shaped by digitalization and sustainability. This study examines how these determinants influence SME growth in Slovenia through a qualitative design with triangulated data. A systematic review of peer-reviewed literature, policy reports, and statistical sources (Scopus, Web of Science, Google Scholar, Eurostat, OECD) was combined with ten semi-structured interviews conducted in March and April 2025 with SME owners and managers across diverse industries in Slovenia. Thematic analysis revealed that digitalization enhances efficiency, innovation, and market expansion, while sustainability drives cost savings, brand differentiation, and competitiveness. Importantly, synergies, such as AI-enabled emission reduction and ERP-supported waste minimization, amplify benefits. However, SMEs also face financial constraints, generational resistance, and regulatory complexity. The findings demonstrate that digital and green transitions are not only complementary but interdependent, underscoring the need for policymakers to integrate both into targeted SME support strategies
Keywords: digitalization; growth determinants; qualitative research; SMEs; sustainability